KEBERADAAN HAK ULAYAT DALAM REFORMASI HUKUM NASIONAL - Devrayno (Jurnal Ilmu Hukum Tambun Bungai, 2016)
Recognition about customary rights owed by customary law community actually can be viewed from several regulation. From Article 33 section (3) Constitutions 1945, where state’s authority aimed to create wealth and prosperous people, theoretically considered as Welfare State, where in this welfare state, individual and community, still owed recognition of their rights, eventhough limited. In agrarian state, land ownership is a needs to fulfill their rights in getting appropriate life. It is shown similarity of ownership and authorization concept by individual, community, or state with similar goal, which is into wealth and prosperous community. However, in its development regarding national law reform, customary rights get recognition as long as it exists, and if it doesn’t exist, the rights wouldn’t be revived. Meanwhile, if it exists, the implementation shall be match with National and State interest, which is based on National Unity. Besides, it shouldn’t conflict with higher Regulations and Laws. That’s why, it needs further review about customary law community with their rights, through unified research, so it could give certainty to existence of customary rights in a customary law community.